Nesting architecture and population structure of the fungus-growing ant cyphomyrmex transversus (Formicidae: Myrmicinae: Attini) in the brazilian coastal zone of ilhéus, bahia - Ramos-Lacau, Lucimeire S. (2012)
The present study provides valuable information about the nesting biology and demographics of Cyphomyrmex transversus (Formicidae: Myrmicinae: Attini). This species has been observed nesting under and inside dry coconuts on the forest ground in the Brazilian coastal zone of Ilhéus, state of Bahia. To investigate the association between C. transversus and coconuts, we surveyed 153 coconuts. Of the surveyed ones, 62 (40.5%) exhibited associated colonies of Cyphomyrmex transversus (one colony per coconut): 53 (85.5%) of the 62 colonies nested under the coconut, and nine (14.5%) nested inside. Distributed among 57 of the coconuts, 17 other ant species were found. The ants most frequently found were Paratrechina longicornis and Camponotus atriceps. Nests of C. transversus were structurally simple, with one principal chamber with small depressions located on the base. Inside the nest cavities, yeast-like fungi formed in polygonal masses. More than one dealate queen was observed in several C. transversus colonies. The population of C. transversus individuals per colony increased according the coconut size. We conclude that the use by the ants of coconut pieces as a part of their nest structure and the occurrence of multiple dealate queens per colony show adaptive flexibility in C. transversus. It may confer a greater capacity for colonization and maintenance of competitive nest densities in the harsh environmental conditions of Brazilian coastal zones. Further studies should consider the social organization of all ant species that nest in coconuts and its effect on colony survival rates and competitive relationships. © 2012 Taylor & Francis Group, LLC.